Alexander Magnus Fromhold von Reutz on Customary Law (Source Study Analysis of the Article “Gewohnheitsrecht und Codification in Russland”) - V. D. Ogorelkova (Сибирское юридическое обозрение, 2025)
The article offers a source-critical analysis of the work Gewohnheitsrecht und Codification in Russland (“Customary Law and Codification in Russia”), written in 1833 by Alexander Magnus Fromhold von Reutz, an eminent Russian legal scholar and one of the founders of the Dorpat School of Law. The article outlines the main content of the work, evaluates its key provisions and conclusions, identifies prospects for further scientific and practical application of its findings, and highlights the scholarly and historical significance of the text. The first part of the article addresses external criticism of the work: it establishes the origin date of the source, its formal attributes, authorship, structure, presentation style, and other characteristics. The second, third, and fourth parts are devoted to internal criticism, which involves identifying philological and factual features of the text, analyzing von Reutz’s scholarly views, and assessing the reliability of his conclusions. The second part also examines the concept of customary law and clarifies its role within the system of legal regulation, including its relationship with statutory law. The third part explores von Reutz’s reflections on legislative activity in Russia during the first half of the 19th century, noting its strengths and weaknesses, and discusses the requirements he formulated for legislators based on his observations. The fourth part analyzes von Reutz’s views on the interpretation of laws and the challenges arising in law enforcement as a result. The author of this article emphasizes the continued relevance of the ideas put forward by A. M. F. von Reutz in his work Gewohnheitsrecht und Codification in Russland, supporting the arguments with examples from modern legal science and practice. The results of this study highlight the prospects for exploring the legacy of pre-revolutionary legal scholarship and adapting some of its provisions to present-day realities.